Tracing the strategic roots of Confucianism in China’s contemporary foreign policy - Yakti, Probo Darono; Susanto, Siti Rokhmawati; Wicaksana, I Gede Wahyu; Afdholy, Nadya (Masyarakat, Kebudayaan dan Politik, 2025)
As China asserts its global role, principles such as harmony (hé), benevolence (rén), and the doctrine of the mean (zhōng yōng) increasingly influence its diplomatic behavior. These values form the basis of what this study calls a “Defensive-Moderate Confucian Approach,” integrating strategic culture, constructivism, defensive realism, and soft power. This article examines how Confucian strategic values shape China’s foreign policy, particularly under Xi Jinping’s leadership. Through case studies of China’s relations with the United States and India, the paper highlights how Confucian ethics guide both cooperative projects like the Belt and Road Initiative and calibrated responses in territorial disputes. While contradictions between moral ideals and strategic interests occasionally emerge, Confucianism remains a key reference in shaping China’s pursuit of order and stability. The article argues that China’s international conduct cannot be fully explained by materialist frameworks alone. Instead, Confucian thought offers a culturally grounded lens for interpreting its foreign policy choices. By doing so, the study contributes to broader discussions in International Relations and Chinese Studies on the enduring impact of historical values in contemporary global politics.